Utilizing a Facebook closed group for EFL e-learning environment: Students’ views - Martha Nandari Santoso (Studies in English Language and Education, 2021)
This study was conducted out of the researcher’s teaching reflection while teaching English as a foreign language (EFL) online class during the pandemic of COVID-19, a time when face-to-face courses had to be converted to online classes. Her choice of educational tool for her EFL e-learning environment utilized a Facebook closed group. Her experiences in utilizing a Facebook closed group for her EFL e-learning environment and the students’ views were the main topics of this study. Eighteen EFL freshmen participants were selected in this study. The researcher used data from a questionnaire with some closed and open-ended questions. The findings indicated that the students found the Facebook closed group a comfortable, practical, and useful e-learning environment. The students’ familiarity with the interface helped them to immediately focus on the class activities instead of learning how to use the tool. Most students viewed the Facebook closed group as positive for class interactions, creative work, opinions, and express feelings. A few dislike voices were related to the display quality of Facebook, the asynchronous and silent communication on Facebook. Accordingly, utilizing a Facebook closed group might be worth considering for learners who have not been adequately prepared with the technology for joining an online class.